2011
DOI: 10.1080/14999013.2011.599097
|View full text |Cite
|
Sign up to set email alerts
|

The Stalking of Psychiatrists

Abstract: Healthcare professionals are known from previous studies to be at risk from stalkers, and mental healthcare professionals, particularly psychiatrists, are thought to be at higher risk. However, no previous large-scale study has investigated this among psychiatrists. This questionnaire-based survey of 10,429 UK psychiatrists aimed to investigate the prevalence, nature and impact of stalking of UK psychiatrists. Of the 2,585 psychiatrists who submitted valid responses, 21% thought they had been stalked; the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The percentage of victimization differed in our sample compared with the categories reported in previous studies: Galeazzi et al (2005) found that the most common type of stalking is by Intimacy Seekers, followed by Resentful stalkers. Whyte et al (2011) found similar results, while research conducted by Purcell et al (2005) showed that stalking by Resentful stalkers was the most common type. Our data revealed that most of the victims indicated rejection (Rejected) as the motivation behind the beginning of a stalking campaign, followed by social incompetence (Incompetent suitors), resentment (Resentful), and some sort of intimacy (Intimacy seekers).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The percentage of victimization differed in our sample compared with the categories reported in previous studies: Galeazzi et al (2005) found that the most common type of stalking is by Intimacy Seekers, followed by Resentful stalkers. Whyte et al (2011) found similar results, while research conducted by Purcell et al (2005) showed that stalking by Resentful stalkers was the most common type. Our data revealed that most of the victims indicated rejection (Rejected) as the motivation behind the beginning of a stalking campaign, followed by social incompetence (Incompetent suitors), resentment (Resentful), and some sort of intimacy (Intimacy seekers).…”
Section: Discussionsupporting
confidence: 53%
“…For example, in a U.K. study among psychiatrists, it emerged that 21% of the sample had been victims of stalking, one third of them by non-patients (Whyte, Penny, Christopherson, Reiss, & Petch, 2011). But HCPs are also prone to victimization in their private life.…”
Section: Prevalence Of Victimization and The Relationship Between Vicmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to hold equally for male and female mental health providers (McIvor et al, 2008;Romans et al, 1996;Whyte et al, 2011), which is notable given that women appear to be the victim of stalking at rates three times higher than men in the general population (Purcell et al, 2004). The available research suggests that between approximately 3% (Sandberg et al, 2002) and 20% (McIvor et al, 2008;Purcell et al, 2005) of mental health professionals will be stalked at some point in their career, with multiple studies placing lifetime prevalence for stalking victimization around 10% (Galeazzi et al, 2005;Gentile et al, 2002;Leavitt et al, 2006;Maclean et al, 2013;Whyte et al, 2011). Given the general consistency in prevalence estimates across studies, the differences that do emerge generally appear to reflect the impact of different definitions of stalking and differences in base rates of STHB in different clinical settings.…”
Section: Prevalence Of Stalking Of Mental Health Professionalsmentioning
confidence: 99%
“…There is a growing body of international research examining clinicians' experiences of STHB by patients in the United States (Gentile, Asamen, Harmell, & Weathers, 2002;Leavitt, Presskreischer, Maykuth, & Grisso, 2006;Romans, Hays, & White, 1996;Sandberg, McNiel, & Binder, 2002;Tryon, 1986), Australia (Purcell, Powell, & Mullen, 2005), New Zealand (Hughes, Thom, & Dixon, 2007), the United Kingdom (Hudson-Allez, 2002;Jones & Sheridan, 2009;Maclean et al, 2013;McIvor, Potter, & Davies, 2008;Whyte, Penny, Christopherson, Reiss, & Petch, 2011), Ireland (Nwachukwu, Agyapong, Quinlivan, Tobin, & Malone, 2012), Canada (Abrams & Robinson, 2011), and Italy (Galeazzi, Elkins, & Curci, 2005;Mastronardi, Pomilla, Ricci, & D'Argenio, 2013). Although stalking statutes vary across jurisdictions, most definitions share an emphasis on repeated, intentional behavior consisting of nonconsensual communication and threats toward a specific individual that would cause a reasonable person to fear for their safety (Mullen, Pathé, Purcell, & Stuart, 1999).…”
Section: Defining Stalking Threatening and Harassing Behaviormentioning
confidence: 99%